Supporting Interorganizational Relationships Management - Diirr, Bruna; Cappelli, Claudia; Oliveira, Douglas; Santos, Gleison; Borges, José Alexandre (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2022: Anais do XVIII Simpósio Brasileiro de Sistemas de Informação, 2022)
Context: Interorganizational relationships have been an option for organizations to remain competitive. They allow resource sharing and collaboration to handle opportunities better. Problem: However, involved organizations may have distinct characteristics, which increase conflicts, influence their alignment, and even lead to interorganizational relationship failure. Solution: To handle such an issue, we outline FIRM, a framework for interorganizational relationships management. IS Theory: A socio-technical theory, which interrelates people-organizations-technology, was adopted for understanding interorganizational relationships and developing FIRM. Method: FIRM was used in a case study of a governmental interorganizational relationship to understand this partnership characteristics/dynamic/issues, besides evaluating FIRM's potential to systematize interorganizational relationships management. It has a descriptive nature, and we adopted a qualitative approach for results analysis. Summary of Results: Results indicate that FIRM adheres to the depicted partnership reality, helps teams during interorganizational relationships management, and minimizes faced issues since all steps/ associated activities were identified or could be practiced to a greater/lesser degree. Contributions and Impact in the IS area: FIRM benefits interorganizational relationships management since it assists involved parties to become more integrated, prepared to interoperate processes/information, and achieve mutual goals. Moreover, a clear understanding of interorganizational relationships’ social perspective allows proposing technologies that support associated needs, work, and collaboration.